Ikony w rosyjskiej polityce dawnej i nowej = ICONS IN RUSSIAN POLITICS – OLD AND NEW - Naumow, Aleksander (Studia religiologica, 2007)
The author of the article discusses the political aspect of the cult of the most worshipped images of Our Lady in the Russian Orthodox Church, namely: Our Lady of Vladimir, Our Lady of Tichvin and her replica Our Lady of Narva, Our Lady of Kazan, Our Lady of the Don River, Our Lady of Pskov, Our Lady of Smolensk and others. He raises the issue of taking advantage of the icons to ensure assistance to the country or its individual cities, in the situation of a military threat. The measure which was resorted to most often was the practice of processions going round an endangered area; in contemporary times, this measure is also supported by the use of airplanes or helicopters. One gets the impression that over centuries, this particular aspect of Russian religiousness has not changed; a good example of this sort of conduct is the decision to declare Virgin Mary - Empress of Russia, the use of icons during World War II, or during the riots in Moscow in the autumn of 1993. In several cases, the author draws attention to the considerable significance of Polish motifs and anti-Western attitudes.